Are Older People Aware of Their Cognitive Decline? Misperception and Financial Decision Making - Fabrizio Mazzonna; Franco Peracchi (Institute of Labor Economics (IZA), 2020)
We investigate whether older people correctly perceive their own cognitive decline, and the potential financial consequences of misperception. First, we document the fact that older people tend to underestimate their cognitive decline. We then show that those who experienced a severe cognitive decline, but are unaware of it, are more likely to suffer wealth losses compared to those who are aware or did not experience a severe decline. These losses largely reflect decreases in financial wealth and are mainly experienced by wealthier people who were previously active on the stock market. Our findings support the view that financial losses among older people unaware of their cognitive decline are the result of bad financial decisions, not of rational disinvestment strategies.
Keywords: J14; J24; C23; 330; aging; cognitive ability; household finance; HRS